Impact of volcanic ash deposition on foliar productivity and insect herbivory in northern Patagonia deciduous forests - Chaneton, Enrique J. (2014)
Fil: Chaneton, Enrique J. Universidad de Buenos Aires. Facultad de Agronomía. IFEVA-CONICET; Argentina.